2015
DOI: 10.1542/peds.2014-1915
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Outcomes of Fetal Alcohol Syndrome in Adulthood

Abstract: BACKGROUND AND OBJECTIVE: Primary disabilities in children prenatally exposed to alcohol have a major impact on their daily life. It is suggested that these issues persist into adulthood, but few studies have addressed the outcome in adults with prenatal exposure, especially those with fetal alcohol syndrome (FAS). The aim of this follow-up study was to investigate outcome variables, such as education, employment, health, and criminal acts, in 79 adults diagnosed with FAS. METHODS:We carried out a national reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 36 publications
6
97
1
2
Order By: Relevance
“…Moreover, the adults with FAS had not been the victims of crime to a larger extent than the comparison group had. The results in this study confirmed those of previous studies (Famy et al, 1998;Rangmar, Hjern et al, 2015) reporting on psychiatric problems among individuals with FAS/D.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the adults with FAS had not been the victims of crime to a larger extent than the comparison group had. The results in this study confirmed those of previous studies (Famy et al, 1998;Rangmar, Hjern et al, 2015) reporting on psychiatric problems among individuals with FAS/D.…”
Section: Discussionsupporting
confidence: 92%
“…There are limited published controlled studies of noradrenergic reuptake inhibitors Crossover RCT quantitative study. n = 4; 5-12 years FAS or pFAS and ADHD − Test group given 0.6 mg/kg Methylphenidate − Control group given lactose or vitamin C as placebo − Placebo given three times a day for 5 days with a 2-day washout period − Control subjects with ADHD experienced greater improvement with stimulant medication than FASD subjects − FASD children subjects performed worse on several measures when tested on stimulant medication than when tested without a stimulant Rangmar et al [32] 30-year longitudinal study, N = 79 adults with FAS, mean age 32…”
Section: Discussionmentioning
confidence: 99%
“…Several studies based on a variety of data sources show a strong relationship between PAE and mental health problems in adults (O’Connor & Paley, 2009; Streissguth et al, 1996; Famy et al, 1998; Freunscht & Feldmann, 2011; Rangmar et al, 2015; Day et al, 2013; Barr et al, 2006). Streissguth et al, and Famy et al, both examined rates of mental health problems in samples of adults with PAE-related diagnoses and reported that large proportions experienced difficulties in this area.…”
Section: Introductionmentioning
confidence: 99%